Biomarkers of aging-associated chronic inflammation as a prognostic factor for human longevity - Leposavić, Gordana; Stojić-Vukanić, Zorica (Archives of Pharmacy, 2022)
It has been well-established that age-associated low-grade chronic inflammation contributes to the development of a spectrum of chronic diseases, including diabetes mellitus, ischemic heart disease, stroke, cancer, chronic kidney disease, non-alcoholic fatty liver disease and neurodegenerative diseases, which affect the quality of life of the elderly and influence their life span. This phenomenon is suggested to arise due to the weakening of the regulatory mechanisms of the immune response, and the persistence of exogenous and endogenous (reflecting oxidative cell injury) antigenic challenges, so it is referred to as oxi-inflamm-aging. Considering that the development of age-associated chronic inflammation is “silent”, i.e., without clinical signs until the aforementioned complications become apparent, it is important to identify the biomarker(s) or pattern/cluster of biomarkers for this inflammation. It is also important to define new strategies to combat the “silent” damage induced by chronic inflammation. Given that at present there are no reliable biomarkers for chronic inflammation, this review points out the problems in defining biomarker(s) or patterns/clusters of biomarkers for chronic inflammation in order to stimulate further research and points to some possible routes of investigation.
Keywords: longevity; low-grade chronic inflammation; non-communicable diseases; oxi-inflamm-aging; biomarkers of chronic inflammation